Immunoprofiling of leukemic stem cells CD34+/CD38−/CD123+ delineate FLT3/ITD-positive clones. Issue 1 (December 2016) - Al-Mawali, Adhra; Gillis, David; Lewis, Ian
Abstract Background Acute myeloid leukemia (AML) is a heterogeneous clonal disorder presenting with accumulation of proliferating undifferentiated blasts. Xenograft transplantation studies have demonstrated a rare population of leukemia-initiating cells called leukemic stem cells (LSCs) capable of propagating leukemia that are enriched in the CD34+/CD38− fraction. LSCs are quiescent, resistant to chemotherapy and likely responsible for relapse and therefore represent an ideal target for effective therapy. LSCs are reported to overexpress the alpha subunit of the IL-3 receptor (CD123) compared to normal CD34+/CD38− hematopoietic stem cells. It has not been demonstrated whether CD123-positive (CD34+/CD38−) subpopulation is enriched for any clonal markers of AML or any LSC properties. The aims of this study were to investigate whether FMS-like tyrosine kinase (FLT3)/internal tandem duplication (ITD) mutations are present at LSC level and whether FLT3/ITD mutation is confined to LSC as defined by CD34+/CD38−/CD123+ and not CD34+/CD38−/CD123−. Methods Thirty-four AML cases were analyzed by five-color flow cytometry and sequential gating strategy to characterize of CD34+/CD38−/CD123+ cells. These cells were sorted, analyzed by PCR, and sequenced for FLT3/ITD. Results In this study, we confirm significant expression of CD123 in 32/34 cases in the total blast population (median expression = 86 %). CD123 was also expressed in the CD34+/CD38− cells (96 ± 2 % positive) from 28/32 for CD123+ AML. CD123 was not expressed/low in normal bone marrow CD34+/CD38− cells (median expression = 0 %, range (0–.004 %). AML samples were tested for FLT3/ITD (10 positive/25). FLT3/ITD+ AML cases were sorted into two putative LSC populations according to the expression of CD123 and analyzed for FLT3/ITD again in the stem cell fractions CD34+/CD38−/CD123+ and CD34+/CD38−/CD123−. Interestingly, FLT3/ITD was only detected in CD34+/CD38−/CD123+ (7/7) and not in CD34+/CD38−/CD123− subpopulation (6/7). Conclusions This finding shows that FLT3/ITD are present at LSC level and may be a primary and not secondary event in leukemogenesis, and the oncogenic events of FLT3/ITD happen at a cell stage possessing CD123. It shows that CD123 immunoprofiling provides further delineation of FLT3+ LSC clone. This novel finding provides a rationale for treatment involving CD123-targeting antibodies with intracellular FLT3 inhibitors directed against CD34+/CD38−/CD123+. This may result in more effective anti-LSC eradication.